Agency and time poverty: Linking decision-making powers and leisure time of male and female farmers of Central India - Khed, Vijayalaxmi D.; Krishna, Vijesh V. (International Maize and Wheat Improvement Center, 2023)
The present study examines the gender differences in workload and decision-making as well as analyzing the influence of decision-making and other socioeconomic factors on the time use of male and female farmers of central India. Analyzing individual-level data collected in 2019 (347 wheat farming households), we found significant gender differences in the total number of work hours, patterns of time use, and the power to make decisions within the household. Men and women participate equally in productive activities, and women spend more time in domestic work. Land ownership by women and belonging to marginalized castes are found associated with a higher workload for female respondents. These factors have an insignificant effect on the amount of work and leisure time of the male respondents. Irrespective of their higher workload, women’s involvement in decision-making is limited. The decisions over different farming and nonfarming activities and the use of income generated from these activities are made predominantly by the male household head across caste groups. We also observe a trade-off between leisure time for women and their involvement in household-level decision-making. Women with agency had less leisure time than others. Our paper concludes that the decision-making agency for women in the study area comes at a cost, unlike in the case of men, due to the existence of patriarchal social norms. Our study findings create a richer picture of rural women’s nexuses of time poverty and decisionmaking, which have implications for the development and diffusion of laborsaving technologies in agriculture.